EFEKTIFITAS PEMBERIAN ASPIRIN DOSIS RENDAH UNTUK MENCEGAH PREEKLAMSIA DI RSPAL DR. RAMELAN SURABAYA: EFFECTIVENESS OF LOW DOSAGE ASPIRIN TO PREVENT PREECLAMPSIA AT RSPAL DR. RAMELAN - Grace Wijaya (Surabaya Biomedical Journal, 2024)
Background: Preeclampsia is a multisystem disorder in pregnancy. In developing countries, cases of preeclampsia are 7 times higher than in developed countries with a prevalence of 1.8%−18%. First-trimester screening needs to be done in detecting preeclampsia in every pregnant woman and preeclampsia prevention strategies with aspirin have proven effective in previous studies. Research Objectives: To determine the effectiveness of low-dose aspirin administration to prevent preeclampsia at dr. Ramelan for the period 13 June 2019 – 30 September 2021. Research Methods: The research design used in this study was descriptive using a retrospective cohort study. Researchers used secondary data in the form of patient medical records with a total sample of 118 patients. Results: From a total sample of 118 people, 30.5% had preeclampsia and 66.1% of patients who were given low-dose aspirin. Conclusion: Pregnant women who experienced preeclampsia after being given low-dose aspirin were recorded in 31 of 78 patients (39.7%) and pregnant women who experienced preeclampsia when not given low-dose aspirin were recorded in 5 of 40 patients (12.5%).